Variation in perioperative practice in elective colorectal cancer surgery: opportunities for quality improvement - Taylor, John C.; Rossington, Hannah; George, Rina; Alderson, Sarah L.; Quirke, Philip; Thomas, Caroline; Howell, Simon (Discover. Oncology, 2025)
Background Understanding the variation in perioperative care across a population is fundamental to improving the management and outcomes of patients with colorectal cancer. Currently, there is limited individual patient level data available to assess this variation. Therefore, as part of an improvement programme, we conducted an audit to understand perioperative care. Methods Audit items were developed to cover the pre, intra and postoperative phases of the colorectal cancer surgical pathway and collected for patients undergoing an elective procedure. The audit was conducted at 14 Hospital Trusts, participating in the Yorkshire Cancer Research Bowel Cancer Improvement Programme, located in the Yorkshire and Humber region, North of England. Results Information on 216 patients were collected. Functional assessment by Cardiopulmonary Exercise Testing varied across the region (performed in 100% patients at three Trusts, but not at all in six Trusts, P < 0.001). The provision of postoperative high dependency and critical care also varied across the region (in seven Trusts ≥ 80% of patients went to a monitored bed or higher level of care; in three Trusts ≥ 90% of patients received ward care, P < 0.001). The median duration of preoperative starvation varied by Trust (2 to 13 h, P < 0.001). The intraoperative dose of opiate administered to patients varied significantly between Trusts (P < 0.001). Conclusions There is wide variation in both the provision and practice of perioperative care across a large region in the North of England. The findings are informing a programme of improvement science-based work to improve the management and outcomes of patients with colorectal cancer.